Treatment of Unilateral Buccal Crossbite with Mandibular Symphyseal Distraction Osteogenesis - Ozkalayci, N.; Özer, M.; Sümer, M. (Korean Assoc Orthodontists, 2011)
The aim of this report is to present the treatment of a 14-year-old boy with scissors-bite. Mandibular sym-physeal distraction osteogenesis (MSDO) with tooth-supported distractor was performed to expand the mandible, and intermaxillary cross elastics were used. The mandible was expanded approximately 9 mm. Asymmetric widening was done by using cross elastics and MSDO simultaneously. The buccal crossbite was corrected successfully. After a 2-year observation period, widening of the mandible using this procedure was judged to be stable.
Keywords: Appliances; Distraction Osteogenesis; Expansion; Facial Asymmetry